PROBLEM OF THE SOCIAL DISADVANTAGES LEARNER DALAM PERSPEKTIF HIRSCHI’S SOCIAL BOND - Ilyas, Khairul Fahmi (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2019)
The life of adolescents in the era of globalization and modernity has changed very drastically and caused widespread problems and moral decadence. Deviant behavior of students today is not only detrimental to itself but has begun to disturb social society in general. This deviation can occur because they are still in the phase of seeking identity and emotional turmoil. Deviant behavior carried out by school teenagers is caused by weak social control. The purpose of writing this article is to see and analyze the deviant behavior of students by using a social control theory approach. Social bonds are social bonds between individuals and conventional groups (schools, communities, and communities) that can control individuals to conform to the norms in society. In this article, the author uses literacy studies to see students' deviant behavior and social bond theory. The results of the analysis show that students' deviant behavior is caused by a lack of social control or social ties that surround the realm of attachment, commitment, involvement and belief between students and conventional groups such as parents, schools and the community.